Liver fluke‐infested graft used for living‐donor liver transplantation: case report and review of the literature. Issue 6 (25th November 2015) - Capobianco, I.; Frank, M.; Königsrainer, A.; Sipos, B.; Menzel, M.; Sturm, E.; Nadalin, S.
Abstract: Clonorchiasis is a cholangiopathy caused by foodborne trematode parasites, also known as liver flukes. Clonorchiasis is endemic in a wide geographical area extending from Eastern Europe to Southeast Asia. Infested hosts may remain asymptomatic for decades and consequently their liver can become available as a graft. To date, 20 liver transplantations with liver fluke‐infested grafts have been reported in the literature. All of them occurred in Asian countries. We, here, report the first case to our knowledge in the Western world of living‐donor liver transplantation (LDLT) with an Opisthorchis felineus ‐infested graft, and present a review of the literature. A 6‐month‐old girl with decompensated secondary biliary cirrhosis underwent an LDLT with a left lateral graft infested with O. felineus . After prompt diagnosis and adequate therapy, both donor and recipient had an uneventful postoperative course and long‐term follow‐up. Liver grafts infested with liver flukes do not pose a contraindication to liver donation from deceased or living donors, provided that a correct diagnosis and treatment are performed in a timely fashion.